2014
DOI: 10.1016/j.ijpsycho.2014.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Generalized lapse of responding in trait impulsivity indicated by ERPs: The role of energetic factors in inhibitory control

Abstract: Impaired inhibitory control is one of the still debated underlying mechanisms of trait impulsivity. The Cognitive Energetic Model accounts for the role of energetic factors mediating task performance. The aim of the present study was to compare inhibitory control functions of adults with high and low impulsivity by using a modified Eriksen flanker task.Adults were classified as impulsive (n = 15) and control (n = 15) participants based on the Barratt Impulsiveness Scale. Flanker trials had three levels of requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…By contrast, in the case of emotionally arousing stimuli, when information is relevant, it can be argued that nonclinical impulsive individuals are characterized by a compensatory increase in response inhibition. Consistent with this interpretation, longer Nogo-P3 latencies for neutral stimuli in HI than LI individuals were noted, suggesting that individuals with high relative to low impulsiveness are characterized by a lower response inhibition or a slower evaluation of irrelevant stimuli (Polich, 2007;Kóbor et al, 2014). It is also possible that differences in assessing impulsiveness (a self-reported questionnaire vs. RT residual scores) may account for partially discrepant Nogo-P3 results between Ruchsow et al's study and the present study. Furthermore, it should be noted that correlation analyses also revealed that accuracy to emotionally arousing Nogo trials was inversely correlated with Nogo-P3 amplitude in the HI group: the lower the accuracy to Nogo trials, the larger the Nogo-P3.…”
Section: Discussionsupporting
confidence: 78%
“…By contrast, in the case of emotionally arousing stimuli, when information is relevant, it can be argued that nonclinical impulsive individuals are characterized by a compensatory increase in response inhibition. Consistent with this interpretation, longer Nogo-P3 latencies for neutral stimuli in HI than LI individuals were noted, suggesting that individuals with high relative to low impulsiveness are characterized by a lower response inhibition or a slower evaluation of irrelevant stimuli (Polich, 2007;Kóbor et al, 2014). It is also possible that differences in assessing impulsiveness (a self-reported questionnaire vs. RT residual scores) may account for partially discrepant Nogo-P3 results between Ruchsow et al's study and the present study. Furthermore, it should be noted that correlation analyses also revealed that accuracy to emotionally arousing Nogo trials was inversely correlated with Nogo-P3 amplitude in the HI group: the lower the accuracy to Nogo trials, the larger the Nogo-P3.…”
Section: Discussionsupporting
confidence: 78%
“…Other studies found an association between reduced prefrontal activity and higher risk tendency but not with higher BIS scores [Brown et al, ]. In contrast, several studies reported positive correlations between different impulsivity measures and enhanced neural activity in right prefrontal areas and left temporal gyrus [Horn et al, ], overall enhanced neural activity in Go condition [Collins et al, ], as well as significantly enhanced P3 amplitudes in high impulsive subjects [Kóbor et al, ]. Using reaction time variability as a task‐related measure of impulsivity instead of self‐rated questionnaires, Ruchsow et al [] demonstrated that non‐clinical high impulsive subjects compared to low impulsive subjects had significantly reduced Nogo‐P3 amplitudes but no differences in Nogo‐N2.…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggested that while impulsivity is characterized by rapid decisions, a rather long and monotonous task with demanding sustained attention could lead to slower task solving. In the same study, we analyzed the correct responses in a larger sample (Kóbor et al, 2014), where the RT difference between the two groups was in line with the ERP findings. Namely, P3 was delayed in HI participants, and the Lateralized Readiness Potential (LRP) peaked later in the HI group than in the LI group, as well, irrespective of other experimental effects.…”
Section: Discussionmentioning
confidence: 77%
“…In our final sample, ten young adults remained in each group with five males and five females. The data was collected in the same study as reported by Kóbor, Takács, Honbolygó, and Csépe (2014), where stimulus locked ERPs were analyzed for correct trials. The experimental procedures were in accordance with the Declaration of Helsinki, including a signed informed consent, and were approved by the institutional committee of research ethics.…”
Section: Methodsmentioning
confidence: 99%